Ensaio pré-clínico da desintegrina recombinante DisBa-01 na angio-gênese inflamatória induzida por implantes sintéticos em camundongos - Vieira, Puebla Cassini (2014)
Angiogenesis and inflammation act simultaneously in several pathophysiological processes. The interactions with the extracellular matrix (ECM) are required in inflammatory angiogenesis. The non-enzymatic disintegrins comprise a family of peptides, low molecular weight, derived from the venom of snakes, which strongly inhibit the functions of integrins. In this study we evaluated the therapeutic effect of disintegrin DisBa-01, derived from the venom of the snake Rhinocerophis alternatus in inflammatory angiogenesis induced by synthetic implants in mice. Treatment with DisBa-01 inhibited the main key components of fibrovascular tissue induced by implants as inflammation and angiogenesis, without changing the fibrogenic component. This experimental model is the implementation of a synthetic matrix in the subcutaneous tissue of the animal, which induces the formation of fibrovascular tissue rich in inflammatory cells, blood vessels and MEC. The model of synthetic implants, also allows the simultaneous evaluation of inflammation, angiogenesis and tissue repair. The inhibitory effects of DisBa-01 were observed by MPO activity (representing activated neutrophils), NAG activity (representing activated macrophage), the chemokines CXCL -1, MCP-1 and the cytokine TNF- α. The anti-angiogenic activity was observed through the reduction of hemoglobin content, number of vessels, blood flow intra-implant by laser doppler and the levels of VEGF and FGF cytokines. The evaluation of DisBa-01 in multiple parameters provides additional evidence to the therapeutic potential of this disintegrin.